Monoterpenoid‐based preparations in beehives affect learning, memory, and gene expression in the bee brain. (26th July 2016) - Bonnafé, Elsa; Alayrangues, Julie; Hotier, Lucie; Massou, Isabelle; Renom, Allan; Souesme, Guillaume; Marty, Pierre; Allaoua, Marion; Treilhou, Michel; Armengaud, Catherine
Abstract: Bees are exposed in their environment to contaminants that can weaken the colony and contribute to bee declines. Monoterpenoid‐based preparations can be introduced into hives to control the parasitic mite Varroa destructor . The long‐term effects of monoterpenoids are poorly investigated. Olfactory conditioning of the proboscis extension reflex (PER) has been used to evaluate the impact of stressors on cognitive functions of the honeybee such as learning and memory. The authors tested the PER to odorants on bees after exposure to monoterpenoids in hives. Octopamine receptors, transient receptor potential–like (TRPL), and γ‐aminobutyric acid channels are thought to play a critical role in the memory of food experience. Gene expression levels of Amoa1, Rdl, and trpl were evaluated in parallel in the bee brain because these genes code for the cellular targets of monoterpenoids and some pesticides and neural circuits of memory require their expression. The miticide impaired the PER to odors in the 3 wk following treatment. Short‐term and long‐term olfactory memories were improved months after introduction of the monoterpenoids into the beehives. Chronic exposure to the miticide had significant effects on Amoa1, Rdl, and trpl gene expressions and modified seasonal changes in the expression of these genes in the brain. The decrease of expression of these genes in winter could partly explain the improvement of memory. The present study has led to new insights into alternative treatments, especially on their effects on memory and expression of selected genes involved in this cognitive function. Environ Toxicol Chem 2017;36:337–345. © 2016 SETAC